The Efficacy of Hypnosis as a Treatment for Anxiety: A Meta-Analysis. Issue 3 (3rd July 2019) - Valentine, Keara E.; Milling, Leonard S.; Clark, Lauren J.; Moriarty, Caitlin L.
Abstract: This meta-analysis quantifies the effectiveness of hypnosis in treating anxiety. Included studies were required to utilize a between-subjects or mixed-model design in which a hypnosis intervention was compared with a control condition in alleviating the symptoms of anxiety. Of 399 records screened, 15 studies incorporating 17 trials of hypnosis met the inclusion criteria. At the end of active treatment, 17 trials produced a mean weighted effect size of 0.79 ( p ≤ .001), indicating the average participant receiving hypnosis reduced anxiety more than about 79% of control participants. At the longest follow-up, seven trials yielded a mean weighted effect size of 0.99 ( p ≤ .001), demonstrating the average participant treated with hypnosis improved more than about 84% of control participants. Hypnosis was more effective in reducing anxiety when combined with other psychological interventions than when used as a stand-alone treatment.